PENGARUH MANAJEMEN KELAS TERHADAP HASIL BELAJAR PELAJARAN IPS SMP NEGERI 09 PONTIANAK - Winda Safitri; Sri Buwono; Husni Syahrudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstrackThis research aimed to know about "The effect of Class Management  to the social study result at the  seven class SMP Negeri 09 Pontianak". The problem in this study is how is class management in SMP Negeri 09 Pontianak, What are the social study result to the seven class SMP Negeri 09 Pontianak, Is there any influence between class and management on the social  study result to the seven class SMP Negeri 09 Pontianak.  The variables in this study are independent variables and dependent variables, which are independent variables namely class management while the dependent variable is student study result. Sources of data in this study are student study result of social studies subjects, while the method used is descriptive quantitative, the population in this study amounted to 70 students of seven class. Based on the data analysis technique, the regression equation is Y = 14,971 + 0,711X. The results of the T test show that t count> t table is calculated> t table (7.196> 1.995) While the determinant coefficient value is 0.432 which means the percentage of the contribution of management class and infrastructure to student learning outcomes is 43.2%.       Keywords : Management Class, Student Learning outcomes